Derivation of soil Pb/Cd/As thresholds for safety of vegetable planting: A case study for pakchoi in Guangdong Province, China - Fu-rong LI; Dian WEN; Fu-hua WANG; Fang-fang SUN; Xu WANG; Ying-qiong DU; Xiang-xiang LIU; Kai WAN (Journal of Integrative Agriculture, 2019)
Regional guidelines for soil heavy metals, in conjunction with specific crops, are proposed to better assess soil environmental quality. In this study, large amounts of soils with different levels of Pb/Cd/As pollution were collected in Guangdong Province, China, to carry out a pot experiment, which was closer to the actual situation and properties of the heavy metal contaminated soils. Taking the widely planted vegetable pakchoi as the research object, we analyzed the correlations between the Pb/Cd/As concentrations in pakchoi and the total or available soil Pb/Cd/As concentrations and established their optimal regression equations. And then, the total and available soil Pb/Cd/As thresholds for pakchoi were calculated according to the allowable Pb/Cd/As limits in pakchoi and were compared with the current soil assessment standards. Furthermore, a lot of paired vegetable-soil samples in field were collected and their pollution situations were assessed by both the current limit thresholds and the calculated thresholds. Obviously, it was more consistent to assess the Cd and As pollution situation of the vegetable and soil samples with the calculated soil thresholds than the current soil assessment thresholds. It further proved that it was necessary to explore the soil heavy metal thresholds for safety of vegetable in specific regions, which would be more scientific and practical to guide safety production of local agricultural products and effective utilization of soil resources.